Pengaruh Pemasaran Digital dan Brand Image Terhadap Kepuasan Pelanggan Produk Skincare Hanasui di E-commerce Shopee - Maharani Puspita Dewi; Aris Mardiyono; Frans Sudirja; Heru Eko Prasetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of digital marketing and brand image on customer satisfaction of Hanasui skincare products on the shopee e-commerce platform. Customer satisfaction is an important factor in maintaining loyalty and business sustainability, especially amid the increasingly competitive skincare industry in digital platforms. The population in this study consisted of regular morning students of the Faculty of Economics and Business at Universitas 17 August 1945 Semarang from the 2022-2025 cohorts, totaling 333 students. This study used a quantitative approach with a sampling technique using the slovin formula, resulting in 77 respondents. Data were collected through questionnaires using a five-point likert scale and analyzed using multiple linear regression. The results showed that digital marketing has a positive and significant effect on customer satisfaction with a significance value of 0.014, while brand image also has a positive and significant effect with a significance value og 0.001. This study proves that improving digital marketing strategies and strengthening brand image can increase customes satisfaction.